Juvenile variant ossifying fibroma of sinonasal region - Pradhan, Susan; Phuyal, Suman; Shrestha, Dipendra Kumar; Shilpakar, Sushil Krishna (Nepal Journal of Neuroscience, 2020)
Juvenile variant ossifying fibroma of sinonasal region is an extremely rare benign fibro-osseous lesion which is locally aggressive. A 21-year-old male presented with significant proptosis of right eye with stony-hard lump in the middle upper aspect of the right orbit and base of the nose. CT scan of head revealed a non-enhancing expansile lesion in right ethmoidal cells consistent with chronic ethmoidal mucocele. However Magnetic Resonance Imaging of brain revealed enhancing lesion in right ethmoid and frontal sinus extending up to anterior cranial fossa. He underwent right frontal craniotomy with surgical excision of tumor wherein cystic brown tumor of frontal and ethmoidal sinus was found. The procedure was supplemented with endoscopic transnasal approach. Histopathology report suggested an ossifying fibroma. This case highlights the importance of clinical, imaging and histopathological features of ossifying fibroma occurring in the sinonasal tract for better diagnosis and treatment through a multidisciplinary approach.